Detecting offshore wind farm-induced wind wake signatures on sea surface using MODIS data - Yu, Weiye; Guo, Pu; Du, Jianting; Lian, Zhan (Frontiers in Marine Science, 2024)
Introduction Offshore wind farms (OWFs) generate extensive wind wakes in their leeward areas, which can induce marine upwelling and downwelling. These processes significantly affect marine stratification and ecosystems, leaving detectable patterns on the sea surface. Materials and Methods By utilizing MODIS data, we analyzed six representative OWFs worldwide to identify these wake signatures. Result Notably, we observed pronounced signatures near an OWF located in the coastal waters of Jiangsu Province, China. Conversely, no coherent wake signatures were detected at other selected European and Chinese OWFs. Discussion This absence may be attributed to inactive upwelling, weak marine stratification, unsteady wind directions, and land-sea distribution. This research offers a fresh perspective on the environmental impacts of OWFs and, for the first time, underscores the potential of global gridded satellite dataset in detecting OWF-induced wind wake signatures.